Rehydration in the Field - Jon E. Rohde (Indonesian Pediatric Society, 1974)
The clinical efficacy of oral-glucose electrolyte (GE) solutions in the treatment of profound fluid losses in cholera is dramatic testimony to the persistent ability of the intestine to absorb glucose, salt and water in the face of severe diarrhea. Many thousands of patients have been successfully saved from almost certain death by drinking sufficient quantities of rehydration fluid.